Effect of Optimization of TiO2 Electron Transport Layer on Performance of Perovskite Solar Cells with Rough FTO Substrates - Wang, Junqi; Zou, Xiaoping; Zhu, Jialin; Cheng, Jin; Chen, Dan; Bai, Xiao; Yao, Yujun; Chang, Chuangchuang; Yu, Xing; Liu, Baoyu; Zhou, Zixiao; Li, Guangdong (Materials, 2020)
The film quality of the electron transport layer (ETL) plays an important role in improving the performance of perovskite solar cells (PSCs). In order to reduce the effect of rough fluorine-doped SnO2 (FTO)substrate on the film quality of the TiO2 ETL, multiple cycles of spin-coating were employed to realize optimized TiO2 film and improve the performance of PSCs with rough FTO. The results show that TiO2 ETL was optimized most effectively using two spin-coating cycles, obtaining the best performance of PSCs with rough FTO. The carbon electrode-based PSCs were then demonstrated. Our work discusses the feasibility of low-quality rough FTO for the fabrication of PSCs and photodetectors to reduce costs.